Coronary Artery Bypass Grafting Combined with Mitral Valve Correction via Minimally Invasive Approach: Technique Description and Results - Babliak, Dmytro Ye.; Babliak, Oleksandr D.; Yatsuk, Serhii V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To present and analyze the technique of simultaneous coronary artery bypass grafting (CABG) and mitral valve repair or replacement through a minimally invasive approach—left anterior thoracotomy in the 4th intercostal space. Materials and methods. The study was conducted at the Diagnostic and Treatment Center For Children And Adults Of The Dobrobut Medical Network. Between October 2020 and March 2024, 50 patients with combined mitral valve disease and multivessel coronary artery disease underwent surgery via minimally invasive approaches. Patients were operated on through a 6–8 cm skin incision and a left anterior minithoracotomy in the 4th intercostal space. The procedure involved peripheral cardiopulmonary bypass (CPB), aortic cross-clamping, and cold blood cardioplegia. The mitral valve (MV) was approached through the right atrium and interatrial septum. Conventional techniques were used for MV repair/replacement. Results. A total of 50 patients were included in the study. The mean age of the group was 65.1 ± 8.8 years, and 16 (34.0 %) patients were classified as NYHA class III-IV. There were no in-hospital deaths, major postoperative cardiac complications, or bleeding complications requiring revision. No conversions to median sternotomy were required. The mean number of distal anastomoses was 2.4 ± 0.9, including 1 ± 0.2 arterial and 1.7 ± 0.6 venous anastomoses. The operative time, aortic cross-clamp time, and cardiopulmonary bypass time were 335.8 ± 49.3 min, 125.7 ± 24.7 min, and 222.04 ± 38.3 min, respectively. The average length of stay in the intensive care unit was 1.5 ± 0.6 days. Conclusions. This technique allows for simultaneous CABG and mitral valve correction through a single left anterior mini-thoracotomy. The immediate outcomes observed in the first consecutive series of 50 patients demonstrate the safety of this cardiothoracic surgical approach. Further evaluation of the clinical efficacy of this method is warranted, particularly in comparison with similar combined procedures performed through median sternotomy.